Determinants of fraudulent financial reporting: evidence from Malaysia - Suhaily Hasnan,; Rashidah Abdul Rahman,; Sakthi Mahenthiran, (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study examines two issues relating to fraudulent financial reporting in Malaysia. The first issue examines factors involved with fraudulent financial reporting practices; i.e. predisposition (i.e. related party transactions, history of prior violations, founders on board), motive (i.e. economic factor, ownership factor, political factor) and opportunity (i.e. poor corporate governance). Then, the second issue looks into the relationship between earnings management and the occurrences of fraudulent financial reporting. The study uses a matched sample of 53 firms that were convicted of issuing fraudulent financial statements during the period from 1996 to 2007. Our results show that firms with fewer related party transactions, higher number of prior violations, and higher proportion of founders on board are more likely to “tip” over the edge into fraudulent financial reporting. We also find that the corporate environment most likely to lead to fraudulent financial reporting is characterised by accounting practices that are already “pushing the envelope” on earnings management. Furthermore, we find that firms are embroiled in fraudulent financial reporting when non-family and non-foreigners own the company, and when the level of financial distress is high. As expected, our results also show that firms involved in fraudulent financial reporting have significantly poor corporate governance structures whereby the audit quality is lower and outside directors seem overcommitted. However, we find no evidence that firm’s political connection factor or the level of board independence play a significant role in the potential for fraudulent financial reporting.